Boundary vector cells in the subiculum of the hippocampal formation - Lever, C; Burton, S; Jeewajee, A; O'Keefe, J; Burgess, N (Journal of Neuroscience, 2009)
“Boundary vector cells” were predicted to exist by computational models of the environmental inputs underlying the spatial firing patterns of hippocampal place cells (O'Keefe and Burgess, 1996; Burgess et al., 2000; Hartley et al., 2000). Here, we report the existence of cells fulfilling this description in recordings from the subiculum of freely moving rats. These cells may contribute environmental information to place cell firing, complementing path integrative information. Their relationship to other cell types, including medial entorhinal “border cells,” is discussed.
EPrint Processing Status: Full text deposited in DRO